2015
DOI: 10.1111/aos.12799
|View full text |Cite
|
Sign up to set email alerts
|

The genetic variant rs4073 A→T of the Interleukin‐8 promoter region is associated with the earlier onset of exudative age‐related macular degeneration

Abstract: PurposeTo study the association of the single nucleotide polymorphism (SNP) rs4073 in the interleukin‐8 (IL‐8) promoter region with the diagnosis and age of onset of exudative age‐related macular degeneration (AMD) in association with the known genetic risk factors for AMD and tobacco smoking.MethodsMedical records, smoking history and angiograms or fundus photographs of 301 patients with exudative AMD, 72 patients with dry AMD and 119 control subjects were analysed retrospectively. The associations of IL‐8 rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
1
9
0
1
Order By: Relevance
“…When at least one CFH risk allele was present, the population-attributable risk for late AMD was 53 percent (Klein et al, 2013). The strong association with risk alleles of CFH rs1061170 has also been validated in recent studies (Babanejad et al, 2015; Fauser and Lambrou, 2015; Hautamaki et al, 2015). …”
Section: Biomarkers In Heritability and Geneticssupporting
confidence: 54%
See 1 more Smart Citation
“…When at least one CFH risk allele was present, the population-attributable risk for late AMD was 53 percent (Klein et al, 2013). The strong association with risk alleles of CFH rs1061170 has also been validated in recent studies (Babanejad et al, 2015; Fauser and Lambrou, 2015; Hautamaki et al, 2015). …”
Section: Biomarkers In Heritability and Geneticssupporting
confidence: 54%
“…Further genomic studies of this chromosome demonstrated two AMD susceptible loci. One is known as rs10490924, which lies within the gene LOC387715/ARMS2, now known as Age-Related Maculopathy Susceptibility 2 (ARMS2) (Hautamaki et al, 2015; Kanda et al, 2007; Shen et al, 2015). The other, rs11200638, lies within the promoter region of the gene known as High Temperature Requirement Factor A1 (HTRA1) gene (Dewan et al, 2006; Francis and Klein, 2011; Yang et al, 2006).…”
Section: Biomarkers In Heritability and Geneticsmentioning
confidence: 99%
“…ere have been few reports on the relationships between these cytokines/chemokines and age/gender except in several age-related diseases, such as exudative age-related macular degeneration and age-related vocal fold atrophy [25,26]. We have no specific explanation as to why the four cytokines and chemokines were related to age/gender.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, a genetic variant of the IL‐8 promoter region was recently found associated with the earlier onset of exudative AMD (Hautamaki et al. ), thereby further implicating miRNAs to play important roles in the retina.…”
Section: Mirnas In Amdmentioning
confidence: 99%